2016
DOI: 10.1186/s40337-016-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain alterations in anorexia nervosa: a scoping review

Abstract: BackgroundNeuroimaging allows for the identification of brain abnormalities and alterations that are associated with anorexia nervosa (AN). We performed a scoping review to map out the extent and nature of recent research activity on functional magnetic resonance imaging (fMRI) in individuals diagnosed with, or recovered from, AN (AN-REC).Main textA literature search of PubMed, Psychinfo and Embase was conducted using the search terms “anorexia nervosa” AND “functional magnetic resonance imaging.” We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 75 publications
2
27
1
Order By: Relevance
“…Modern neuroimaging technologies allow e in addition to structural analyses e the investigation of functional alterations under conditions of anorexia nervosa (Table 1). Overall, functional magnetic resonance imaging (fMRI) studies indicate altered neural activity across the brain, including the frontal, parietal, temporal and occipital lobes, as well as subcortical structures such as the amygdala, striatum, thalamus and the cerebellum [34]. Despite the growing body of knowledge due to the increase in number of fMRI studies, a clear pathophysiological picture is still to be drawn.…”
Section: Functional Alterations In Anorexia Nervosamentioning
confidence: 99%
See 2 more Smart Citations
“…Modern neuroimaging technologies allow e in addition to structural analyses e the investigation of functional alterations under conditions of anorexia nervosa (Table 1). Overall, functional magnetic resonance imaging (fMRI) studies indicate altered neural activity across the brain, including the frontal, parietal, temporal and occipital lobes, as well as subcortical structures such as the amygdala, striatum, thalamus and the cerebellum [34]. Despite the growing body of knowledge due to the increase in number of fMRI studies, a clear pathophysiological picture is still to be drawn.…”
Section: Functional Alterations In Anorexia Nervosamentioning
confidence: 99%
“…The differentiation between alterations subsequent to the disease/malnourishment and those causally involved is still a big challenge. There are different possibilities to address this question [34], namely first, comparing patients within the first months of their disease with chronically ill patients, second, to investigate acutely ill patients compared to recovered patients, third, comparing recovered patients with healthy controls and fourth, studying patients with anorexia nervosa compared to patients with malnutrition due to any other reason. However, only few studies are available so far applying these suggested study designs.…”
Section: Functional Alterations In Anorexia Nervosamentioning
confidence: 99%
See 1 more Smart Citation
“…Brain structural and functional alterations have also been largely reported in AN (Frank, 2015;Fuglset, Landro, Reas, & Ro, 2016;Gaudio, Wiemerslage, Brooks, & Schioth, 2016). Voxel-based morphometry (VBM) studies have however focused on adult patients, finding a reduced grey matter (GM) volume in many brain regions involved in the pathophysiology of AN.…”
mentioning
confidence: 99%
“…As adjuncts to traditional ED treatment techniques, top-down and bottom-up "neurophysiological interventions have been shown to diminish symptoms associated with ED" [31], contradicting feelings of helplessness and fear, and facilitating a sense of empowerment [13].…”
Section: Neurophysiological Interventions Integrate Mind Brain Bodymentioning
confidence: 99%